Proteomics-based network pharmacology and molecular docking reveal the potential mechanisms of 5,6,7,4′-tetramethoxyflavone against HeLa cancer cells - Qiang You; Lan Li; Haiyan Ding; Youping Liu (Heliyon)
Recent research has highlighted the therapeutic potential of citrus-derived dietary 5,6,7,4′-tetramethoxyflavone (TMF) against HeLa cancer. Our study aims to elucidate its mechanisms of action through proteomics analysis, network pharmacology, and molecular docking. The results suggested that TMF demonstrated efficacy by upregulating CD40, CD40L, Fas, Fas-L, HSP27, HSP60, IGFBP-1, IGFBP-2, IGF-1sR, Livin, p21, p27, sTNFR2, TRAILR2, TRAILAR3, TRAILR4, XIAP, p-Sre, p-Stat1, p-Stat2 p-c-Fos, p-SMAD1, p-SMAD2, p-SMAD4, p-SMAD5, p-IκBα, p-MSK1, p-NFκB, p-TAK1, p-TBK1, p-ZAP70, and p-MSK2, while downregulating p-EGFR, p-ATF2, p-cJUN, p-HSP27, p-JNK, and p-GSK3A. These targets are primarily involved in MAPK, apoptosis, and TNF signaling pathways. Notably, p21, p27, EGFR, SMAD4, JNK, ATF2, and c-JUN merged as pivotal targets contributing to TMF's anti-cancer efficacy against HeLa cells. This study is first to delineate the potential signaling pathways and core targets of TMF in treating of HeLa cancer, paving the way for further exploration of TMF's medical potential.